Single nucleotide polymorphism of pparγ, enpp1 and capn-10 genes in type 2 diabetes mellitus patients with and without coronary artery disease in a Malaysian tertiary hospital / Darishiani Paramasivam - Darishiani, Paramasivam (2016)
Type 2 Diabetes mellitus (T2DM) and coronary artery disease (CAD) are two major lifestyle disorders in the world. T2DM and CAD share several common risk factors, mainly genetic and environmental. The Single Nucleotide Polymorphisms (SNPs) of the PPARγ (Pro12Ala), ENPP1 (K121Q) and CAPN-10 (SNP-63), respectively have been identified as the key regulators of glucose and lipid metabolism. These polymorphisms control the protein synthesis in multiple metabolic, biochemical and molecular pathways. The aim of this study was to investigate the PPAR-γ, ENPP1 and CAPN-10 genes polymorphisms as genetic risk factors for T2DM and CAD in the Malaysian population. A total of 360 subjects between the age of 35 and 85 years were recruited in this study. Out of the 360 subjects, 120 were T2DM patients, recruited from the outpatient clinic at UMMC; 120 were T2DM patients with CAD (T2DM+CAD), recruited from cardiac clinic at UMMC and the other 120 were healthy hospital staff. DNA from the blood samples was extracted using QIAamp DNA Mini Kits. SNP of PPARγ, ENPP1 and CAPN-10 were determined by polymerase chain reaction (PCR) and restriction fragment length polymorphisms (RFLP). The analysis showed that the Pro allele of PPARγ (Pro12Ala) is risk factor for T2DM (OR: 2.11, 95% CI: 1.10-4.04, p=0.020) and T2DM+CAD (OR: 3.56, 95% CI: 1.74-7.29, p=0.001) among the Chinese but not among the Malays and Indians. The K allele of ENPP1 (K121Q) and C allele of CAPN-10 (SNP-63) do not increase the risk of T2DM or T2DM+CAD in all three ethnic groups. We conclude that, SNP of PPARγ (Pro12Ala) gene could be a genetic risk factor for T2DM and CAD in the Chinese population but not in Malay and Indian population.